Analysis of the Role of Judicial Institutions in Sharia Economic Law Enforcement in Indonesia - Mappasessu Mappasessu (Journal of Islamic Economy, 2024)
This study aims to analyze the concrete role of judicial institutions in the enforcement of sharia economic law in Indonesia. The main focus is to understand how the Religious Courts, District Courts, and Supreme Courts handle sharia economic cases and identify the challenges faced in the process. The research method used is a qualitative approach with a case study design. Data were obtained through in-depth interviews, observations, literature studies, and documentation analysis. The results of the study show that the Religious Court has a central role in the application of sharia principles in banking, insurance, and sharia capital market cases. Collaboration between Religious Courts and District Courts is important in handling complex cases involving aspects of national law and sharia. However, several challenges such as the lack of special training for judges, limited resources, and unclear regulations are still the main obstacles in the enforcement of sharia economic law. This research makes a theoretical contribution by enriching the literature on sharia economic law and practicality by providing recommendations to increase the effectiveness of sharia economic law enforcement. The main recommendations include increasing training and capacity building of judges, harmonization of regulations, and the use of information technology in case management. Thus, this research is expected to support the creation of a fairer and more effective legal system in the enforcement of sharia economic law in Indonesia.